THE RELATIONSHIP OF THE LONG TIME OF 3 MONTHS INJECTIVE CONTRACT USE WITH MENSTRUAL DISORDERS AND WEIGHT INCREASE AT THE PRATAMA RESTU BUNDA CLINIC, JAKARTA, 2023 - Ratnasari, Diah Yulianti; Yuningsih, Sukarni Setya (HEARTY, 2025)
Background The Family Planning (KB) Program is a series of population development and quality human resource development aimed at controlling population quantity on a national scale (Dewi et al., 2022). According to the results of the 2021 family data collection, BKKBN, shows that the prevalence rate of PUS for family planning participants in Indonesia in 2021 is 57.4%. Based on provincial distribution, the highest prevalence rates for family planning use are South Kalimantan (67.9%), Bangka Belitung Islands (67.5%), and Bengkulu (65.5%), while the lowest are Papua (15.4%), Papua West (29.4%) and Maluku (33.9%). Meanwhile, DKI Jakarta Province is not recorded in the graph above because the data sourced from CARIK JAKARTA has not been integrated into the data from the 2021 family data collection, BKKBN.The side effects of injectable birth control that are often complained about are menstrual disorders and weight gain. Purpose of WritingTo find out the relationship between the duration of using contraceptive injections for 3 months with menstrual disorders and weight gain at the Pratama Restu Bunda Clinic, Jakarta in 2023. Research methodsusing a quantitative type of research with a cross sectional approach, the population of this study was active family planning acceptor participants at the Pratama Restu Bunda Clinic, Jakarta, taken from data in December 2023. The sample size was 51 respondents using the technique of purposive sampling. Analyze data using analysis univariate And Bifarious analysis using the chi-square test. Research resultThe results of statistical tests with the chi-square test show thatThe 95% confidence level obtained by p (Sig) is 0.009, p value (sig) < α (0.009 < 0.05) and it can be concluded that there is a relationship between the length of use of 3-month contraceptive injections and menstrual disorders in acceptors of 3-month injectable contraceptives at the Pratama Restu Bunda Clinic, Jakarta. Year 2023. Conclusions and recommendations is hoped that future researchers can review the relationship between using 3-month injectable birth control with menstrual disorders and weight gain so that future researchers can find other factors in using 3-month injectable birth control.